Detection of hunting pits using airborne laser scanning and deep learning - Lidberg, William (Swedish University of Agricultural Sciences, 2024)
This is training and testing data for the detection of hunting pits in airborne laser data. The data is split into three parts. 1: Data for transfer learning with radar imagery and impact craters on the moon. 2. Data for training and testing of the machine learning model. 3: Data from a separate demonstration area used to evaluate the model.

The lunar data (1) were used to pre-train a machine learning model before training on the real data of hunting pits from earth (2). The demonstration data was used to visually evaluate the result of the final model.
All code used to create this dataset and train the machine learning models can be found here: https://github.com/williamlidberg/Detection-of-hunting-pits-using-airborne-laser-scanning-and-deep-learning The code is also included in the file "code.zip"

Det här är tränings och test-data för att detektera fångstgropar i laserdata med hjälp av maskininlärning. Datat är uppdelat i tre delar. 1: Data för förträning med hjälp av radarbilder och kratrar på månen. 2: Data för träning och testning av maskininlärningsmodellen. 3: Data över ett demonstrationsområde där modellen testas.

Datat från månen (1) användes för att förträna en maskininlärningsmodell och datat från jorden (2) användes för att träna modellen på att kartera fångstgropar på jorden. Demonstrationsområdet användes för att visuellt utvärdera resultatet.

All kod som används för att ta fram datat samt träna modellerna finns här: https://github.com/williamlidberg/Detection-of-hunting-pits-using-airborne-laser-scanning-and-deep-learning koden finns också i filen "code.zip"
Detection of hunting pits using airborne laser scanning and deep learning
Training data for hunting pit detection
Keywords: PRESERVATION OF CULTURAL PROPERTY; KULTURMINNESVÅRD; machine learning; maskininlärning; farm forestry; lant- och skogsbruk; cultural environment; kulturmiljö; remote sensing; fjärranalys; Pit Trap; Computer Sciences; Datavetenskap (datalogi); Computer graphics and computer vision; Datorgrafik och datorseende; Physical Geography; Naturgeografi; Geotechnical Engineering and Engineering Geology; Geoteknik och teknisk geologi; History; Historia; Society; Samhälle och kultur